Detrimental Effects of Space Flight on the Lumbar Spine May Be Correlated to Baseline Degeneration: Insights From an Advanced MR Imaging Study - Bokhari R; Bisson DG; Fortin M; Vigouroux M; Cata JP; Hwang KP; Chen MM; Ceniza-Bordallo G; Ouellet JA; Ingelmo PM (Journal of Pain Research)
Rakan Bokhari,1 Daniel G Bisson,2 Maryse Fortin,3 Marie Vigouroux,4 Juan Pablo Cata,5,6 Ken-Pin Hwang,7 Melissa M Chen,8 Guillermo Ceniza-Bordallo,9 Jean A Ouellet,2,10 Pablo M Ingelmo3,10,11 1Division of Neurosurgery, Department of Surgery, College of Medicine, King Abdulaziz University, Jeddah, Saudi Arabia; 2Department of Pediatric Orthopedics, McGill University, Montreal, QC, Canada; 3Department of Health, Kinesiology & Applied Physiology, Concordia University, Montreal, QC, Canada; 4Edwards Family Interdisciplinary Center for Complex Pain, Montreal Children’s Hospital, Montreal, QC, Canada; 5Department of Anesthesia and Perioperative Medicine, The University of Texas – MD Anderson Cancer Center, Houston, TX, USA; 6Anesthesiology and Surgical Oncology Research Group, Houston, TX, USA; 7Department of Imaging Physics, The University of Texas – MD Anderson Cancer Center, Houston, TX, USA; 8Department of Neuroradiology, The University of Texas – MD Anderson Cancer Center, Houston, TX, USA; 9Department of Radiology, Rehabilitation and Physiotherapy, Faculty of Nursing, Physiotherapy, and Podiatry, University Complutense of Madrid, Madrid, Spain; 10Alan Edwards Centre for Research on Pain, McGill University, Montreal, QC, Canada; 11Research Institute, McGill University Health Center, Montreal, QC, CanadaCorrespondence: Guillermo Ceniza-Bordallo, Email gcenizaprof@gmail.comIntroduction: Pain in lower back is a common condition reported by astronauts, both during and after space missions. Investigating the alterations in the spine and the mechanisms driving these changes is essential for a deeper understanding of how microgravity impacts the human spine. This knowledge could also open pathways for therapeutic or preventive interventions. Nevertheless, there is a limited evidence regarding changes in intervertebral discs (IVDs) due to space travel.Materials and Methods: In this study, 2 astronauts were enrolled in a space travel. Before the space flight, a lower back magnetic resonance imaging (MRI) scan was performed. We repeated an MRI instantly after 17-days space travel, and again 3 months after landing. The water content and glycosaminoglycan (GAGs) levels in the lumbar IVDs were evaluated using DIXON water-only phase imaging and T1rho MRI sequences. Additionally, alterations in the size and quality of the paraspinal muscles (PSMs), including fatty infiltration, were examined.Results: Varied alterations were observed in the IVDs and PSMs of both astronauts. One astronaut experienced a reduction in water and GAGs content, while the other showed an increase. These changes in the IVDs following spaceflight appeared to be linked to the degree of baseline degeneration. Regarding the PSMs, differences in size and fatty infiltration also varied between the two astronauts. Notably, these changes had not stabilized by the final follow-up at 3 months.Conclusion: Our findings offer initial evidence indicating that even brief exposures to microgravity might be linked to biochemical alterations in IVDs and changes in the quality of PSMs, which could continue evolving for more than 3 months after returning from space.Keywords: MRI, neuroimaging, spaceflight, spine, low back pain